Karnasrava : An Analytical Study - Sheenam; Fiaz, Shamsa (International Research Journal of Ayurveda & Yoga, 2024)
Ayurveda the ancient science of health has immense knowledge about human body and various types of diseases. Our great seers described myriad of diseases with the causes, pathogenesis and treatment. Urdhvajatrugata (ENT) Roga is described vary vastly in classics. Karnasrava is one such disease described by all ancient acharyas of Ayurveda. The term Karnasrava means flow, oozing, dropping, exudates or discharge through ear. According to Sushruta, Karnasrava may arise due to head injury, diving in water and suppuration or bursting of an abscess. Charaka included Karnasrava as a symptom under the four types of karanrogas.